Prodromal Markers of Parkinson's Disease in Patients With Essential Tremor - Wang, Xi-Xi; Feng, Ya; Li, Xuan; Zhu, Xiao-Ying; Truong, Daniel; Ondo, William G.; Wu, Yun-Cheng (Frontiers in Neurology, 2020)
Background: Essential tremor(ET) is manifested as an isolated syndrome of bilateral upper limb actiontremor. Parkinson’s disease (PD)is the second most common neurodegenerative disease, with typical motorsymptoms of bradykinesia, rigidity and resting tremor. ET-PD describes the new-onset of PD in ET patients. Recently, numerousstudies ofepidemiology, genetics, pathology, clinicalfeatures, and neuroimaging studies are challenging the idea that ET isan isolated disease, suggestingthat patients with ET have the tendency to develop PD.Methods: In this review article, we collectedrecent findings thatreveal prodromal markers of PD in patients with ET. Results: SN hyperechogenicityserves as a prodromal marker for predicting the development of PD in patients with ET and provide a reference for therapeutic strategies. Additionalpotential markers include other neuroimaging, clinical features, heart rate, and genetics,whileothers lack sufficient evidence. Conclusion:In consideration of the bare researchof PD in patients with ET, we are still far from revealing the prodromal markers.Substantia nigrahyperechogenicitymay enable further exploration of the relationship between ET and PD and the search for pathogenesis-based therapies.